Exploring effects of environment density on heterogeneous populations' level of service perceptions. (June 2019) - Sharifi, Mohammad Sadra; Christensen, Keith; Chen, Anthony; Song, Ziqi
Abstract: It is necessary to design and evaluate the effectiveness of walking facilities to accommodate the needs of all pedestrian groups, including individuals with disabilities. The Americans with Disability Act (ADA) standard requires that each facility or part of a facility constructed by, on behalf of, or for the use of a public entity shall be designed and constructed in such manner that the facility or part of the facility is readily usable by individuals with disabilities. The Highway Capacity Manual (HCM) defines walking facility performance using a qualitative measure describing operational conditions, or level of service (LOS). However, how closely pedestrian LOS thresholds correspond to pedestrian groups' perceptions is questionable. To overcome these limitations, a controlled large-scale walking experiment involving individuals with disabilities was conducted at Utah State University (USU). A temporary circuit with the necessary walking facilities was constructed using eight-foot, self-standing walls. In total, 202 (160 without and 42 with disabilities) individuals were recruited to participate in the experiments, with participants asked to pass through the circuit repeatedly. Individuals were tracked using the camera system, and trajectory data extraction was accomplished using a software platform suite. During each experimental session, some participants were randomly selected and asked to complete a questionnaire assessing their walking experience. Using both trajectory and survey data sources, this study explored how a heterogeneous mix of pedestrians perceive and evaluate the operational performance of walking facilities. Specifically, an ordered statistical approach was applied to investigate the effects of environmental density on pedestrians' perceptions. The results indicated that individuals with disabilities were less tolerant of extremely congested environments. Furthermore, the analysis demonstrated that the LOS criteria provided in HCM is inadequate in quantifying the service performance of walking facilities based on the actual perceptions of individuals who participated in the controlled experiment. The findings are expected to improve operational guidelines employed to assess walking facility performance.